The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1037/0278-7393.24.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention during encoding in implicit and explicit memory.

Abstract: In 5 experiments, participants read study words under conditions of divided or full attention. Dividing attention reduced performance on the general knowledge test, a conceptual implicit test of memory. Likewise, dividing attention reduced conceptual priming on the wordassociation task, as well as on a matched explicit test, associate-cued recall. In contrast, even very strong division of attention did not reduce perceptual priming on word-fragment completion, although it did reduce recall on the matched expli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
205
6
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(237 citation statements)
references
References 130 publications
(322 reference statements)
20
205
6
6
Order By: Relevance
“…Other studies have indicated that divided attention reduces priming to a far lesser extent than explicit memory (e.g., Rajaram et al 2001). These relationships concern implicit memory for perceptual stimulus attributes (perceptual priming), whereas conceptual priming is reduced by divided attention to a similar extent as explicit memory (Mulligan 1998;Light et al 2000). Moreover, behavioral estimates of explicit familiarity are reduced by divided attention, but to a lesser extent than estimates of explicit recollection (Yonelinas 2001).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other studies have indicated that divided attention reduces priming to a far lesser extent than explicit memory (e.g., Rajaram et al 2001). These relationships concern implicit memory for perceptual stimulus attributes (perceptual priming), whereas conceptual priming is reduced by divided attention to a similar extent as explicit memory (Mulligan 1998;Light et al 2000). Moreover, behavioral estimates of explicit familiarity are reduced by divided attention, but to a lesser extent than estimates of explicit recollection (Yonelinas 2001).…”
Section: Discussionmentioning
confidence: 95%
“…In prior studies, divided attention during encoding has been found to disproportionately influence explicit memory compared to implicit memory. Indeed, priming is often unaffected by divided attention despite marked reductions in explicit memory (e.g., Mulligan 1998). Other studies have indicated that divided attention reduces priming to a far lesser extent than explicit memory (e.g., Rajaram et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mulligan and Hartman (1996) demonstrated that the presence ofa digit-detection task during encoding ofwords greatly reduced later memory for the words as measured by a conceptual implicit memory test (category exemplar production) and two explicit tests (category cued recall and word-fragment cued recall) but not by a perceptual implicit memory test (word-fragment completion). Mulligan (1998) showed that 267 …”
mentioning
confidence: 99%
“…Divided attention during study serves to degrade later episodic memory. 11 However, we found that subjects performed better after studying with divided attention than with full attention, again implicating visual fluency rather than episodic memory. In addition, these novel effects were only obtained when strategic episodic retrieval processing was limited via response signals during the recognition test, indicating that relatively automatic decisions were essential.…”
Section: Article Addendummentioning
confidence: 58%